2016
DOI: 10.1007/s12559-016-9407-7
|View full text |Cite
|
Sign up to set email alerts
|

Toward Self-Referential Autonomous Learning of Object and Situation Models

Abstract: Most current approaches to scene understanding lack the capability to adapt object and situation models to behavioral needs not anticipated by the human system designer. Here, we give a detailed description of a system architecture for self-referential autonomous learning which enables the refinement of object and situation models during operation in order to optimize behavior. This includes structural learning of hierarchical models for situations and behaviors that is triggered by a mismatch between expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Another example is the work in [ 17 ], in which the authors propose a brain-inspired cognitive architecture for autonomous learning of knowledge representation. This architecture presents key concepts in terms of acquiring knowledge based on behavioral needs and reusing patterns to explain new situations.…”
Section: Introductionmentioning
confidence: 99%
“…Another example is the work in [ 17 ], in which the authors propose a brain-inspired cognitive architecture for autonomous learning of knowledge representation. This architecture presents key concepts in terms of acquiring knowledge based on behavioral needs and reusing patterns to explain new situations.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the central role of astrocytes in information processing [5] has been envisaged decades ago by Galambos in his "glial-neuronal theory of the brain" [53]. Finally, my hypothesis that the astrocyte functions as a mediator for self-reflexive agents implies that it is able to interpret the environment only in terms of "its own" previously acquired situation models and has to integrate previous and novel models in a consistent behavior-related way [54]. Considering proemial counting it represents a self-reflexive or self-referential operation.…”
Section: Discussionmentioning
confidence: 88%
“…Importantly, Haikonen [67] showed that a mismatch between behavioral outcome according to current sensory input signals and the expected outcome based on previously learned internal models triggers an adaptation of object and situation models. Moreover, Damerov and coworkers [66] developed a model of self-referential autonomous learning applying concepts similar to those in my proposed model [68]. Accordingly, a situation is rather the task-driven interpretation of a scene referring also to behavioral models, action outcomes, and internal states of the subject, such as intentions and goals…”
Section: Discussionmentioning
confidence: 97%
“…Approaches to implement brain-inspired architectures for autonomous agents are faced with the problem of adapting behavioral needs not anticipated by the human modeler [65] [66]. Importantly, Haikonen [67] showed that a mismatch between behavioral outcome according to current sensory input signals and the expected outcome based on previously learned internal models triggers an adaptation of object and situation models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation